2016
DOI: 10.1007/s00381-016-3261-5
|View full text |Cite
|
Sign up to set email alerts
|

An interictal EEG can predict the outcome of vagus nerve stimulation therapy for children with intractable epilepsy

Abstract: VNS is a well-tolerated and effective adjuvant therapy in pediatric patients with intractable epilepsy. Notably, patients with focal epileptiform discharges alone rather than those with generalized epileptiform discharges maybe better candidates for VNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…We analyzed age at seizure onset within each group in six studies [15,16,[18][19][20]24], including 416 patients; we found no significant difference between the good responders and poor responders (p = 0.530, SMD = 0.075, 95% CI: -0.159 to 0.310, heterogeneity test: Chi 2 = 7.44, p = 0.190, I 2 = 32.8%, Fig. 3).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We analyzed age at seizure onset within each group in six studies [15,16,[18][19][20]24], including 416 patients; we found no significant difference between the good responders and poor responders (p = 0.530, SMD = 0.075, 95% CI: -0.159 to 0.310, heterogeneity test: Chi 2 = 7.44, p = 0.190, I 2 = 32.8%, Fig. 3).…”
Section: Discussionmentioning
confidence: 94%
“…At 6 m, 1, 2, 3, 4, 6 and 12 years after implantation, 33.99, 43.42, 46.50, 63.31, 52.71, 54.64, 70.37 and 82.90% of patients exhibited > 50% reduction of seizure frequency after VNS. In the 14 trials [7,[10][11][12][14][15][16][17][18][19][20][21][22]24], including a total of 906 participants, analysis age at VNS implantation as a predictor for VNS outcome within each group, we found no significant difference between the good responders and poor responders (p = 0.305, SMD = -0.075, 95% CI: -0.220 to 0.069; heterogeneity test: Chi 2 = 12.20, p = 0.526, I 2 = 0%, Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations